Quality of the parent-child interaction in young children with type 1 diabetes mellitus: study protocol - Aanstoot Henk-Jan; Emons Wilco HM; van Bakel Hedwig JA; Pouwer Frans; Nieuwesteeg Anke M; Odink Roelof; Hartman Esther E (BMC, 2011)
Abstract Background In young children with type 1 diabetes mellitus (T1DM) parents have full responsibility for the diabetes-management of their child (e.g. blood glucose monitoring, and administering insulin). Behavioral tasks in childhood, such as developing autonomy, and oppositional behavior (e.g. refusing food) may interfere with the diabetes-management to achieve an optimal blood glucose control. Furthermore, higher blood glucose levels are related to more behavioral problems. So parents might need to negotiate with their child on the diabetes-management to avoid this direct negative effect. This interference, the negotiations, and the parent's responsibility for diabetes may negatively affect the quality of parent-child interaction. Nevertheless, there is little knowledge about the quality of interaction between parents and young children with T1DM, and the possible impact this may have on glycemic control and psychosocial functioning of the child. While widely used global parent-child interaction observational methods are available, there is a need for an observational tool specifically tailored to the interaction patterns of parents and children with T1DM. The main aim of this study is to construct a disease-specific observational method to assess diabetes-specific parent-child interaction. Additional aim is to explore whether the quality of parent-child interactions is associated with the glycemic control, and psychosocial functioning (resilience, behavioral problems, and quality of life). Methods/Design First, we will examine which situations are most suitable for observing diabetes-specific interactions. Then, these situations will be video-taped in a pilot study (N = 15). Observed behaviors are described into rating scales, with each scale describing characteristics of parent-child interactional behaviors. Next, we apply the observational tool on a larger scale for further evaluation of the instrument (N = 120). The parents are asked twice (with two years in between) to fill out questionnaires about psychosocial functioning of their child with T1DM. Furthermore, glycemic control (HbA1c) will be obtained from their medical records. Discussion A disease-specific observational tool will enable the detailed assessment of the quality of diabetes-specific parent-child interactions. The availability of such a tool will facilitate future (intervention) studies that will yield more knowledge about impact of parent-child interactions on psychosocial functioning, and glycemic control of children with T1DM.